THE EFFECT OF HOUSEHOLD WASTE MANAGEMENT ON FLOOD PREVENTION IN BEKASI REGENCY - Marningot Tua Natalis Situmorang (Teunuleh Publisher, 2021)
This research was conducted on housewives whose houses were affected by the flood on January 1, 2020 in Bekasi Regency. The selection of respondents using purposive sampling with simple random sampling on 5 (five) housing in Bekasi Regency which was affected by the flood disaster. The research sample was 120 people, which consisted of the direct behavior category and indirect behavior. These two categories were identified after socialization on waste and household waste management was carried out. Based on statistical tests, there is a partially significant influence between knowledge of waste management on people's behavior in managing household waste. The results of statistical tests also show that there is a partially significant influence between attitudes about waste management on waste management behavior. In addition, the statistical test results show that there is a simultaneous significant influence between knowledge and attitudes about waste management on the behavior of Bekasi Regency residents managing household waste to cope with flooding. From the results of this study, it can be concluded that the majority of Bekasi Regency residents have good knowledge, attitudes and behavior towards household waste management such as not littering and not burning garbage. The results also found that household waste was not the main cause of flooding in Bekasi Regency.